1965
DOI: 10.1530/jrf.0.0100273
|View full text |Cite
|
Sign up to set email alerts
|

Strain Differences in Susceptibility of Mice and Rats to Cadmium-Induced Testicular Damage

Abstract: The observations of Pa\l=r%v\\l=i' \zek& Zahor (1956) and Pa\l=r%v\\l=i' \zek (1957a, b) Zahor, 1956; Pa\l =r%v\\l =i ' \zek,1957a, b;Meek, 1959;Kar & Das, 1960;Gunn et al., 1961). Animals were killed 48 hr after the injection of cadmium.A total of 130 mature (8-week-old) male mice, composed of eighteen different inbred strains and one random bred strain (CD-1, derived from HaM/ICR Swiss mi ce)\s=deg\ were tested. Following the administration of CdCl2, necrosis was seen consistently in the random-bred CD-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(16 citation statements)
references
References 6 publications
(6 reference statements)
1
15
0
Order By: Relevance
“…In contrast, genetic factors could account for only 13% of the variance in male blood cadmium levels (126). This question leads to the suggestion that mutations in specific genes might contribute to the cadmium burden in the reproductive tract of some infertile men and is supported by studies in animal models (127)(128)(129)(130)(131)(132).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, genetic factors could account for only 13% of the variance in male blood cadmium levels (126). This question leads to the suggestion that mutations in specific genes might contribute to the cadmium burden in the reproductive tract of some infertile men and is supported by studies in animal models (127)(128)(129)(130)(131)(132).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, the testis is particularly sensitive to Cd, at dosages that do not cause hepatic damage (26). Several inbred strains of mice are resistant to Cd-induced testicular damage (27). More recent studies have shown that the C3H/He mice are more sensitive to Cd-induced hepatotoxicity than are the DBA/2 mice strain.…”
Section: Discussionmentioning
confidence: 99%
“…In response to Cd, the testis undergoes massive necrosis. However, several strains of mice, which fail to develop testicular necrosis after Cd exposure, have been identified; they are termed Cd-resistant as opposed to the susceptible strains (Chiquone and Suntzeff 1965;Gunn et al 1965). It has been hypothesized that in rodents, administration of Cd induces Mt protein(s) in the testicular tissue and that this process diminishes the toxic effect on this organ by sequestering certain amounts of Cd (Nordberg 1971).…”
Section: Introductionmentioning
confidence: 99%